Promise and Provisos of Artificial Intelligence and Machine Learning in Healthcare - Bhardwaj A (Dove Medical Press, 2022)
Anish Bhardwaj Departments of Neurology, Neurosurgery, Neuroscience, Cell Biology and Anatomy, University of Texas Medical Branch (UTMB), Galveston, TX, USACorrespondence: Anish Bhardwaj, Departments of Neurology, Neurosurgery, Neuroscience, Cell Biology and Anatomy, University of Texas Medical Branch (UTMB), 9.128 John Sealy Annex, Route 0539, 301 University Blvd, Galveston, TX, 77555, USA, Tel +1-409-772-8068, Email anbhardw@UTMB.EDUAbstract: Artificial Intelligence (AI) and Machine Learning (ML) promise to transform all facets of medicine. Expected changes include more effective clinical triage, enhanced accuracy of diagnostic interpretations, improved therapeutic interventions, augmented workflow algorithms, streamlined data collection and processing, more precise disease prognostication, newer pharmacotherapies, and ameliorated genome interpretation. However, many caveats remain. Reliability of input data, interpretation of output data, data proprietorship, consumer privacy, and liability issues due to potential for data breaches will all have to be addressed. Of equal concern will be decreased human interaction in clinical care, patient satisfaction, affordability, and skepticism regarding cost-benefit. This descriptive literature-based treatise expounds on the promise and provisos associated with the anticipated import of AI and ML into all domains of medicine and healthcare in the very near future.Keywords: artificial intelligence, machine learning, cost-benefit, healthcare